Changes in intraepidermal nerve fiber and Langerhans cell densities in the plantar skin of rats after mercuric chloride exposure. Issue 1 (7th December 2017) - Sun, Binbin; Fan, Shuangyi; Yao, Kai; Li, Yifan; Huang, Xusheng
Abstract: Mercury and its compounds possess strong neurotoxicity and patients with mercury poisoning often report pain and numbness in the distal extremities that conform to the "stocking–glove" pattern. However, no study has investigated whether damage to small nerve fibers is associated with mercury poisoning. The aims of the present study were to evaluate the effects of different doses of mercury chloride (HgCl2 ) on intraepidermal nerve fibers density (IENFD) and Langerhans cells (LCs) in the plantar skin of rats and to assess the possible relationship between changes in IENFD and sensory testing. Male Sprague–Dawley rats were divided into three experimental groups and administered HgCl2 solutions via gavage at three different doses (4.25, 8.5, and 17 mg/kg/day) for 21 days. Subsequently, behavioral tests and pathological changes in IENFD and LCs were assessed at three different time points (1, 2, and 3 weeks). Rats in all three HgCl2 groups exhibited varying degrees of weight and hair loss. Thermal hypersensitivity was evident in all the HgCl2 groups (for middle‐2w subgroup, p < 0.05). Mechanical sensitivity tests revealed hyposensitivity in all the HgCl2 groups except the high‐1w subgroup. Significant decreases in IENFD (for the high‐1w, middle‐1w, low‐2w, and low‐3w subgroups, p < 0.05) and significant increases in the density of LCs (except for the low‐1w and high‐2w subgroups, all p < 0.05) were found in all groups after HgCl2 exposure. An association analysis revealed a significant correlation between the decrease in IENFD and the increase in LCs densities (r = −0.573, p < 0.01). The present study demonstrated a decrease in IENFD and an increase in LCs density in the plantar skin of rats after HgCl2 poisoning, indicating that damage of the small nerve fibers occurs after mercury poisoning.